Analysis of the influence of different control modes on the transient power characteristics of DFIG. Issue 1 (January 2021) - Li, Zhiping; Cao, Na
Abstract: In the event of failure, the doubly-fed Induction Generator (DFIG) with low voltage ride through (LVRT) ability will have different effects on the parallel network characteristics due to the different control mode. In order to analyze the influence of different control modes on the transient power characteristics of DFIG, three kinds of transient response states of wind power system under grid fault are modeled by using power superposition principle based on RSC / GSC controller sampling link and PWM small inertia link, and the accurate transient power response models of different control modes are obtained. The accuracy of the model is verified by simulation with PSCAD/EMTDC, and the influence of control mode on system frequency stability is analyzed.